DECREASED ATHLETE MOTOR SKILLS: BEFORE AND AFTER ACTIVITY CORONAVIRUS DISEASE (COVID-19) PANDEMIC. - Herli Pardilla; Raffly Henjilito; Putri Asilestari; Iqbal Husnayadi (Inspiree)
The purpose of the study. is study was to look at the impact of pandemic 19 before and after Activity Coronavirus disease (B-A COVID-19P) on the performance of athletes' motor skills (MS)